Deserts and Desertification - Zhu, Yajuan; Luo, Qinghong; Liu, Yuguo (IntechOpen, 2022)
A desert is an ecosystem in an arid zone in which sand dunes cover the land and sandstorms often occur. Although desert vegetation is sparse, it plays an important role in ecosystem structure and function. Desertification is one of the most severe environmental problems today. Land desertification can be controlled through many measures, such as eco-villages, eco-agriculture, biodiversity conservation, and the combination of engineering and biology. This edited volume provides new insights into the pattern of desert ecosystems and the progress of desertification control. It is a useful resource for researchers in ecology, forestry, and land desertification control.